2012
DOI: 10.1007/s10404-012-0940-8
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modeling of multiphase flows in microfluidics and micro process engineering: a review of methods and applications

Abstract: This article presents a comprehensive review of numerical methods and models for interface resolving simulations of multiphase flows in microfluidics and micro process engineering. The focus of the paper is on continuum methods where it covers the three common approaches in the sharp interface limit, namely the volumeof-fluid method with interface reconstruction, the level set method and the front tracking method, as well as methods with finite interface thickness such as color-function based methods and the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
197
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 364 publications
(208 citation statements)
references
References 454 publications
(539 reference statements)
0
197
0
Order By: Relevance
“…The first two tasks, collectively denoted multi-phase flow methods, have been studied computationally in a remarkable volume of work, as summarized in a recent review by Wörner [68]. Prominent surveys for each of the main families of methods are (Level-set methods) Sethian & Smereka [55], (Front-tracking) Tryggvason et al [66], (Volume fraction methods) Scardovelli & Zaleski [54] and (Phase field methods) Anderson et al [2].…”
Section: Surfactantsmentioning
confidence: 99%
“…The first two tasks, collectively denoted multi-phase flow methods, have been studied computationally in a remarkable volume of work, as summarized in a recent review by Wörner [68]. Prominent surveys for each of the main families of methods are (Level-set methods) Sethian & Smereka [55], (Front-tracking) Tryggvason et al [66], (Volume fraction methods) Scardovelli & Zaleski [54] and (Phase field methods) Anderson et al [2].…”
Section: Surfactantsmentioning
confidence: 99%
“…Liquid-gas slug flow in small capillary tubes and microchannels is important in heat transfer applications [1][2][3][4], micro-reaction systems [5,6], and microfluidic control [7,8]. Bretherton [9] pioneered theoretical analysis of single bubble motion in a rigid round channel under a lubrication assumption that at low Capillary numbers, viscous forces only affect the static interface profile near the wall.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Magnini et al [23,24] investigated microchannel flow boiling in this regime, and found evaporation from the liquid film to be the dominant mechanism of heat transfer. More detailed accounts of the development of theoretical and numerical models can be found in recent review articles on the subject [8,25,26]. Most prior numerical studies, as summarized by Talimi et al [26], were limited to Ca > ~0.005, although flow behavior at smaller…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations